Careers in Food Science: From Undergraduate to Professional - Hartel, Richard W.; Klawitter, Christina; Thiel, Abbey (Cham : Springer International Publishing : Imprint: Springer, 2023)
Careers in Food Science provides detailed guidelines for students and new employees in the food industry to ensure a successful start to their career. Every step towards a rewarding career in this rapidly evolving industry is covered, from which classes to take in college and which degrees to earn, to internships, and finally how to land, and keep, the first job. This book also provides day-to-day examples of what to expect from the many jobs available to help students decide what to do and where to go. This second edition includes nine new chapters covering research chefs, food systems, social justice, food waste, start-ups, sustainability, and management. Several new authors offer fresh perspectives. Provides detailed guidelines for students as well as new employees in food industry; Includes perspectives from school years through how to succeed at new job; Written by individuals who have just gone through that experience or who are working in that particular sector.
Section 1: Introduction -- 1. Introduction: Career Preparation for the Food & Beverage Industry -- 2. The Equilibrium of Life-Career Planning -- 3. First Jobs for Food Science -- Section 2: The undergraduate student experience -- 4. Making the Most of Your Undergraduate Experience -- 5. Campus Career Services and Centers -- 6. Professionalism and Leadership -- 7. Is Food Science Right For Me? The Transfer Experience -- 8. The Decision to Pursue an Internship -- 9. IFT Student Association -- Section 3: A successful industry career -- 10. Finding and negotiating a job -- 11. Employer expectations/Managing corporate life -- 12. Could a small company be for you? -- 13. A successful industry career or Making your way in a company -- Section 4: Careers with a degree in food science -- 14. Quality -- 15. Production management -- 16. Product development -- 17. Technical sales -- 18. R&D -- 19. Regulatory and food law -- 20. Careers in Traceability -- 21. Using food science in special interest groups -- 22. Food for Good: Leveraging Food Science to Feed the World -- 23. Careers that combine Culinary and Food Science -- 24. Entrepreneurship and Consulting: Taking a Different Path -- 25. Careers in Sensory Science -- 26. Food Science in Community-Based Food Systems -- 27. Working for a Startup Company -- 28. Careers in Sustainability -- 29. A Career in Management -- Section 5: The graduate student experience -- 30. Is grad school right for me? -- 31. Finding and getting into the right grad program -- 32. The transition from undergraduate to graduate student -- 33. Faculty expectations of graduate students.
Keywords: Food science; Chemistry; Food Science; Chemistry